Introduction: Major Databases with Historical Longitudinal Population Data: Development, Impact and Results - Sören Edvinsson; Kees Mandemakers; Ken R. Smith (Historical Life Course Studies)
Over the last 60 years several major historical databases with reconstructed life courses of large populations have been launched. The development of these databases is indicative of considerable investments that have greatly expanded the possibilities for new research within the fields of history, demography, sociology, as well as other disciplines. In this volume spanning seven articles, eight databases are included that had a wide impact on research in various disciplines. Each database had its own unique genesis that is well described in the articles assembled in this volume. They inform readers about how these databases have changed the course of research in historical demography and related disciplines, how settled findings were challenged or confirmed, and how innovative investigations were launched and implemented. In the end we explore how research with this kind of databases will develop in future.